PDA mobile learning using indoor intelligent wireless whiteboard - Aburas, Abdurazzag Ali; Khalifa, Othman Omran (2007)
The information and the educational technologies has rapidly changed in recent years. The application of information technology typically Mobile has become as new technology that can enhance the quality of learning. More class time and assignments in introduction to information technology should be dedicated. This paper reports on the designing the interface of a mobile learning PDA based on wireless whiteboard classroom architecture. Developing an adaptive and context aware mobile learning system is presented. Therein, the proposed technique would definitely enhance the lecturer's hand written notes to integrate PDAs in classroom. Future development approaches for systems supporting learning environments is considered.